(untitled) (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2021)
The role of road transport in logistics transportation is determined and peculiarity of logistics transportation which performs by military formations is shown, namely a wider range of changes in operating conditions. Attention is drawn to the fact that both single trucks and road trains are mostly used for road transportation. The advantages of using road trains in comparison with single automobiles during performing transportations are noted. It is shown that in the modern automotive industry the field connected with the use of multi-axle heavy-duty road trains and articulated self-propelled platforms actively develops. Widespread and further improvement of these vehicles is due to a large number of objective factors. Contradictions between the existing constructions of road trains and the requirements for the efficiency of automobile transportations especially military have been established. One of the field of efficiency increase of automobile transportations using road trains with active trailer links is specified. The existing constructions of road trains with active trailer links are analyzed. Features of a construction, advantages and disadvantages of active links of road trains of various types of energy transfer are defined. The efficiency of various drive system transmissions of active axles of trailer links, namely: mechanical, hydrostatic and electrical to achieve maximum passability and dynamism in a wide range of operating conditions of road trains. It is substantiated that the most promising is the use of electrical (or electromechanical) drive on the wheels of trailer links of the road train which will simplify the construction of the transmission and futher increase the passability and dynamism of the road train by separate control of individual wheels. Keywords: road train, active trailer, transmission, trailer link, passability.